PERLINDUNGAN HUKUM TERHADAP MASYARAKAT ATAS TINDAKAN PENGGELEDAHAN TELEPON SELULER OLEH KEPOLISIAN PADA SAAT MELAKUKAN RAZIA - Teuku Maudriansyah; Rugun Romaida Hutabarat (Fakultas Hukum Universitas Tarumanagara, 2022)
A search is an investigator's action to carry out an inspection of the house as well as an examination ofthe body or clothing to look for objects that are strongly suspected of being on the body or being takenalong, for confiscation. When carrying out a search, the police must comply with the Criminal ProcedureCode so that there are no human rights violations. In this regard, the Police have made many coerciveef orts and have also ruled out the Criminal Procedure Code in conducting a search. The issues in thisresearch is how is the legal protection for the community regarding the search for cell phones by thepolice during raids. Based on the result of this research is that Unscrupulous members of the police haveclearly violated the provisions contained in article 33 of the Criminal Procedure Code (KUHAP) andprivacy that everyone has. The police should carry out their duties according to procedures.Furthermore, it can be used as a preventive measure related to human rights violations and privacy whichare essentially an integral part of ef orts to provide legal certainty to the community, as well as being analternative step in resolving a legal problem.